Class Control Efforts to Discipline Students in Learning - Jarkasih Jarkasih; Khoirul Azkia Faisal AS; Muhammad Raihanzein; Tarsono Tarsono (CV. Rayyan Dwi Bharata, 2024)
This research is one way that teachers are trying to get the class to be more focused on learning. This exploration is a subjective clear review to decide the reasons for the issues looked by educators in overseeing class VII understudies at the Bina Insani Leles Coordinated Islamic Center School, Garut Rule. This study is a type of field research that involves seventh-grade students. Information assortment strategies through perception, surveys and documentation. Information can be dissected from each subject considered, specifically the school head, PAI subject educator and class VII understudies. The teacher's efforts to keep the classroom calm, learning can be followed easily, there is no chaos or noise, students can play alone or with colleagues, they can leave when teaching and learning activities are going on, and most importantly, student discipline is getting better. Techniques that can be utilized incorporate executing learning systems, homeroom the executives and spatial preparation, inspiring understudies, messing around or mixed with ice breaking to condition understudies. In essence, classroom management also has an effect on the ongoing learning process in the form of classroom conditioning. Learning will be disrupted and educational objectives will be difficult to achieve if teachers are unable to master classroom management techniques.